PERLINDUNGAN ANAK BERBASIS PANTI ASUHAN DI PANTI ASUHAN YATIM PUTRI ISLAM YAYASAN RM SURYOWINOTO DAN PANTI ASUHAN YATIM JAMASBA - , Agus Abdul Mughni, Krisdyatmiko, S.Sos, M.Si ([Yogyakarta] : Universitas Gadjah Mada, 2011)
Recent cases of violentce and discriminatn against children are alarming.We witness a large number of cases of children being abandoned,childen not having education,children living on the steet an homeless an so fort. Very little efforts have been taken to save these children from their misery..While Indonesian government has been managing numeros programs in supporting their wellbeing,the existing efforts are unable t deal with the large extent of the issues relating to childen. In an attempt to enhance those homeless childres wellbeing partnership and cooperation are required, bot amongst governments institutions and amogst communities initiatives. One of communities participation have been taking place such foundations and abot which his research is focusing are the RM Suryowinoto Orphanage and Jamasba Orphanage,both are in Bantul district. This research examines the services and guardianship practices and management for homeless and parentless children undertake in both orphanages. This project employs a qualitative research participants or informants who were involved in this study were the organizers of both orphanages and the foster children hosted in both foundation. They were selected using key person and snow ball sampling technique. The data was collected using in depth interviews,observation and documentation. The data is divided in primay data that includes statements and attitudes of the informants anf sedconday data tha includes the documents and recods related to service and guardianship for foster children. Findings of the research show that both orphanages provide comprehensive services.These include physical services and non physical services. Some of the services that canbe categorized as safeguard for children based on orphanage include: the provision of basic needs. The provision of health-welleing needs, support for religious expression, he provision of employment âoriented education and the establishmentof support group within the orphanages. The benefits of children safety programs include.: protectingchildren from some harmful social risks, securing childrens life in the future,the fulfillment of childrens needs and the orphanages acting as family for the children. However the study also notes some important issues that require a serious attention. Firstly. more professional services and management are required In boorphanages including well trained and professional social workers. Secondly ,both orphanages need to provide more space for their foster children in expressing their aspration and thought. Thirdly, a wider publication informing the founations beyond their local is requiredo cover a wider population of homelessand parentless children. Fourthly, both orphanage need to deveop more innovatie programs including those related to mre advance technology of information (IT) so that they are capable of respondin o the job market demands white regard to employment opportunity fo foster children.